ANALISIS PERBANDINGAN PERHITUNGAN DAYA DUKUNG TANAH DARI HASIL UJI SONDIR/CONE PENETRATION TEST (CPT) PADA PROYEK GEDUNG KPPN TANJUNG BALAI - Ivan Kristian Wijaya Telaumbanua; Amir Hamzah; Simorangkir, Simon Petrus Hamonangan (Jurnal Bidang Aplikasi Teknik Sipil dan Sains (BATAS), 2025)
Infrastructure development in Indonesia, including in Tanjung Balai, requires careful planning to ensure adequate soil carrying capacity, so soil investigation is an important step in this process. This research aims to analyze the comparative calculation of soil bearing capacity from the results of the Sondir/Cone Penetration Test (CPT) on the KPPN Tanjung Balai Building project. The method used includes primary data collection through CPT testing at two location points, as well as analysis using the Meyerhof method, Schermann, and Terzaghi. The analysis results show that the soil bearing capacity value varies depending on the method used. On point 5,46S-01, calculation of soil bearing capacity using the method Meyerhof produces a value of 6.24 t, 12,44 t with method Schermann, And 7,12 t with method Terzaghi. Meanwhile, on point S-02, the soil bearing capacity value obtained is 5,15 t with method Meyerhof, 26,74 t with method Schermann, And 4,46 t with method Terzaghi.